Pertanggung Jawaban Notaris Berkenaan Dengan Kebenaran Substansi Akta Otentik - Wayan Paramarta Jaya (RechtIdee, 2017)
Notary as a position has its own authority which is regulated with the rule of law to make an authAentic deed. This authority is described in Article 15 of Law Number 2 Year 2014 as amendments from UUJN. However, this authority is unperfect due to not arranged authority to Notary's for investigation, so the notary is unable to investigate the thruth of material document data fom confrontist is true or not. Condition like that often drag the Notary into legal issues in both criminal and civil problems. The purpose of this thesis research is divided into two, that is general purpose of an academic and special purpose is to examine and analyze how the notary accountability in making authentic deeds and to know and understand the legal consequences of authentic deeds made by the notary when the parties provide false data. This study is a normative juridical research using statute approach and conceptual approach. Based on the analysis of legal material obtained, basically a notary has responsibility for the formalities of an authentic deed and has no responsibility for the material of the contents the authentic deed except in the relass deed. Notaries can be requested of accountability if the Notary is proven to have committed administrative, civil and criminal violations. Notary must be responsible in terms of Administrative Law, Civil Law, that is in accordance with the provisions of sanctions contained in Article 84 and 85 on Amendment of UUJN and code of ethics, but in UUJN and UUJN Change Law does not regulate the existence of criminal sanctions. Notary cant be sought for criminal liability if there is a loss to one of the parties as a result of false documents from another party, since the notary only records what the parties have submitted to the deed. Such false statements shall be the responsibility of the parties, not the responsibility of the notary, unless such fraud or deceit originates from the Notary itself, a notary may be sought for criminal responsibility in accordance with article 263, 264, 266 of the Criminal Code.